تطوير دارة التحكم بالمفاتيح الإلكترونية لقالب أحادي الطور يُستخدم في النظام الكهروشمسي - أيمن نبهان (Tishreen University, 2018)
This research is centered on the design of the electronic switch control circuit for a single phase inverter to generate a sine wave output voltage similar to the network voltage in terms of frequency and value. The design has the advantage of a pure sine wave with low harmonics and low cost. The technique used is the "sinusoidal pulse width modulation" technique generated by the microcontroller. To ensure the accuracy of the designer inverter and the driving circuit, we performed several tests on different AC loads. The proposed inverter model improved the output waveform and reduced the dead time of the control signal to less than 63 microseconds, witch reducing the harmonics. In addition, the results of the practical test were compared with the simulation results and there was a good agreement. يتمحور العمل في هذا البحث حول تصميم دارة التحكم بالمفاتيح الالكترونية لقالب أحادي الطور بهدف توليد جهد خرج ذو موجة جيبية تماثل جهد الشبكة العامة من حيث التردد والقيمة، يمتاز التصميم بالحصول على موجة جيبية نقية بتوافقيات قليلة وبتكلفة منخفضة. التقنية المستخدمة هي تقنية " تعديل عرض النبضة الجيبي"PWM"  المولدة عبر المُتحكّم الصغري. للتأكد من دقة عمل القالب المصمم ودارة القيادة تم القيام بعدة اختبارات على أحمال متناوبة ذات استطاعة مختلفة، حيث استطاع نموذج القالب المُقترح تحسين شكل موجة الخرج وتخفيض الزمن الميت لإشارة التحكم إلى أقل من 63 ميكرو ثانية مما يساهم في خفض التوافقيات الضارة، بالإضافة إلى أنه تم مقارنة نتائج الاختبار العملية مع نتائج المحاكاة وكان هناك تطابق جيد.